Synthesis Of Antibacterial Cream Based On Allium Sativum As Topical Delivery - Henika, Fany; Khalid, Dr Rozida (Jurnal Zarah, 2013)
This study was conducted to produce a topical delivery system which has an active ingredient which can be used for treatment of skin diseases such as acne and common skin disease. In this study, four cream formulation were prepared. Three of four cream formulations contained Allium sativum extract 0.35%, 0.5% and 0.65%. Infrared spectroscopic analysis was performed on four samples of different extracts of Allium sativum. In addition, Allium sativum extract and four samples of different creams have alsodone testing for antibacterial activity. In this study, Sthaphylococcus aureus and Escherichia coli were used as microorganism. The Results showed that samples of fresh methanol extract Allium sativum provide better antibacterial activity compared to the three other samples. Four samples of cream with different percentage of active ingredients showed have no antibacterial effect after antibacterial activity testing been done. However, in terms of quality, the samples of the cream produced a good quality, based on the value of pH, viscosity and stability for 3 weeks of storage